2008
DOI: 10.1055/s-0028-1082894
|View full text |Cite
|
Sign up to set email alerts
|

Successful Management of Foot Drop by Nerve Transfers to the Deep Peroneal Nerve

Abstract: Traumatic damage to the common peroneal nerve due to sharp injury, gunshot wound, sciatic nerve tumor, radiculopathy, or hip replacement surgery may result in foot drop. We present an alternative strategy for reanimation of foot drop following deep peroneal nerve palsy, successfully restoring voluntary movement. Fourteen consecutive patients with deep peroneal nerve injuries resulting in foot drop underwent nerve transfer of functional fascicles of either the superficial peroneal nerve or of the tibial nerve a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
82
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(89 citation statements)
references
References 12 publications
3
82
1
1
Order By: Relevance
“…The two patients with Grade M0 ankle dorsiflexion were an average age of 68 years (range, 66-70 years) with an average time to surgery of 7.5 months (range, 6-9 months). When comparing the patients in the present study with those in the study of Nath et al [12] study, with M3 or greater return of ankle dorsiflexion after nerve transfer, there was no difference in the average age of the patients or in the average time to surgery. Both studies showed a trend toward a more favorable outcome in younger patients and patients who underwent earlier surgery, although the number of patients in our study was too small for statistical analysis (Table 2).…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…The two patients with Grade M0 ankle dorsiflexion were an average age of 68 years (range, 66-70 years) with an average time to surgery of 7.5 months (range, 6-9 months). When comparing the patients in the present study with those in the study of Nath et al [12] study, with M3 or greater return of ankle dorsiflexion after nerve transfer, there was no difference in the average age of the patients or in the average time to surgery. Both studies showed a trend toward a more favorable outcome in younger patients and patients who underwent earlier surgery, although the number of patients in our study was too small for statistical analysis (Table 2).…”
Section: Discussionmentioning
confidence: 48%
“…Larger prospective clinical studies are needed to confirm the success of nerve transfers to obtain ankle dorsiflexion and the variables that could potentially predict favorable or unfavorable function after partial tibial nerve transfers to the anterior tibialis motor branch in the treatment of peroneal nerve injuries after high-energy trauma to the knee. Nath et al [12] reported on seven of nine patients who successfully regained BMRC Grade 4 or greater ankle dorsiflexion after tibial nerve transfers for deep peroneal nerve injuries. The remaining two of the nine patients obtained Grade M0 ankle dorsiflexion after the transfer.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, we used antigravity muscle strength as a clinically meaningful recovery, and this likely resulted in higher percentages of patients defined as having recovered. In addition, patients in our series were treated with a variety of interventions, including neurolysis and nerve and tendon transfers, which have been previously demonstrated to improve recovery and function [9,16,21]. Despite surgical treatment, the peroneal nerve has a poor intrinsic ability for recovery, perhaps as a result of its variable and diminished intraneural blood supply [15].…”
Section: Discussionmentioning
confidence: 99%
“…77,132,138 Contrary to the most popular form of treatment (cyst resection) or even a more radical approach (nerve resection with or without nerve grafting or nerve transfer), 14,17,18,23,24,48,57,78,91,95,104,105,108,155,162,164,171 we recommend treating the articular branch connection and/or the joint. Even with isolated nerve transfer, 91 the articular branch remains connected to the neighboring joint, which would conceivably allow for cyst recurrence. We have shown that addressing the articular branch by ligating or disconnecting it near the joint or treating the articular pathology prevents intraneural cyst recurrence.…”
Section: Surgical Managementmentioning
confidence: 99%